Bioeconomy futures: Expectation patterns of scientists and practitioners on the sustainability of bio‐based transformation - Biber‐Freudenberger, Lisa; Ergeneman, Candan; Förster, Jan Janosch; Dietz, Thomas; Börner, Jan (Sustainable development (Bradford, West Yorkshire, England), 2020)
Economic sectors relying on the use of biological organisms, processes, and principles to create products and services are expected to experience accelerated growth due to innovation in the bioeconomy. Associated benefits and risks for sustainable development are increasingly subject to societal debate. We compiled expectation patterns from a global survey with bioeconomy experts and a systematic literature review identifying areas of consensus and controversy across dimensions of the sustainable development goals (SDG). Positive connotations dominated in both expert opinions and the scientific literature, but the level of consensus varied across sectors of the bioeconomy and in relation to applied methodological approaches (scientific literature) and type of employer (experts). In both sources, we found more differentiated views on potential impacts of bioeconomic development pathways on sustainability in more established bioeconomy-related discourses, which indicates that expectation patterns in more recent fields of bio-based innovation are subject to early “hype cycle” dynamics. Our findings suggest the need to systematically mainstream sustainability risk appraisals across relevant application contexts in technology impact assessments for the bioeconomy.